Bioetanol dari Singkong sebagai Sumber Energi Alternatif - Endang Lovisia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
Abstract: This study aims to produce bioethanol from cassava and determine the yield of fermentation, a crop of distillation, and analysis of the amount of bioethanol paid per kilogram of cassava. The research method used is descriptive quantitative. The results showed that the distillation process was carried out three times, and the average was taken as a sample of 0.59 liters. In conclusion, based on the results obtained from the fermentation of 66.34%, distillation yield of 2.78%, and bioethanol per kilogram of cassava, as much as 0.098 liters/kg. Keywords: Bioethanol, Yield, Cassava